You're the man [compact disc] - Gaye, Marvin (Tamla, 2019)
The first-ever planned 'lost' Tamla/Motown album from Marvin Gaye. Includes three tracks newly mixed by SaLaAM ReMi. The album also includes a rare long version of Marvin Gaye's canceled Christmas single, as well as an unreleased vault mix of its instrumental B-side, and a new essay by Marvin's biographer, David Ritz. It was the album originally proposed to follow up the monumental What's Going On. The release coincides with the 60th anniversary of the Motown label.